2019
DOI: 10.1002/nop2.257
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of breastfeeding self‐efficacy among women attending an urban postnatal clinic, Uganda

Abstract: Aim The aim of this study was to determine the factors associated with breastfeeding self‐efficacy among postnatal women in Kampala, Uganda. Methods This was a descriptive cross‐sectional study that was conducted among women attending a postnatal clinic at a teaching hospital in Kampala. Three hundred and eighty‐four postnatal women were randomly selected to respond to an interviewer‐administered questionnaire. We used the Breastfeeding Self‐Efficacy scale (BFSES) to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 21 publications
(43 reference statements)
2
11
2
2
Order By: Relevance
“…Multidisciplinary actions developed during the prenatal and postpartum periods strengthen bonds between teams and users, facilitate the care line's implementation, and promote integrality 33 . In keeping with previous studies 26,35 , most of the interviewees reported not having received information about BF during the prenatal period. It is common to have not received any teaching or demonstration of BF by any health team professional, although most dentists have stated that they frequently carry out health education activities with the theme of BF during the prenatal period.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Multidisciplinary actions developed during the prenatal and postpartum periods strengthen bonds between teams and users, facilitate the care line's implementation, and promote integrality 33 . In keeping with previous studies 26,35 , most of the interviewees reported not having received information about BF during the prenatal period. It is common to have not received any teaching or demonstration of BF by any health team professional, although most dentists have stated that they frequently carry out health education activities with the theme of BF during the prenatal period.…”
Section: Discussionsupporting
confidence: 62%
“…Self-e cacy expresses how much effort mothers dedicate to BF, how they respond to any challenges, and how long they persevere in BF in the face of obstacles 26 . Self-e cacy is a dominant factor in satisfaction with BF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other studies, we based the classification of breastfeeding self-efficacy on the median of the total score [23,24]. The use of median was supported by previous studies using either mean and or median as the cut-off point to categorise low and high breastfeeding self-efficacy [24][25][26]. We classified mothers who scored less than the median as having a low self-efficacy on breastfeeding, mothers who scored equal to or above the median as having a high self-efficacy.…”
Section: Outcome Variablementioning
confidence: 86%
“…As in other studies, we based the classi cation of breastfeeding self-e cacy on the median of the total score [25,26]. Previous studies supported using either the mean and or the median as the cut-off point to categorize low and high breastfeeding self-e cacy [26][27][28]. We classi ed mothers scoring less than the median as having a low self-e cacy on breastfeeding, and those scoring equal to or above the median as having a high self-e cacy.…”
Section: Outcome Variablementioning
confidence: 99%